2022
DOI: 10.3389/fnut.2022.852907
|View full text |Cite
|
Sign up to set email alerts
|

New Alternatives to Milk From Pulses: Chickpea and Lupin Beverages With Improved Digestibility and Potential Bioactivities for Human Health

Abstract: There is a strong demand for plant-based milk substitutes, often low in protein content (<1.5% w/v). Protein-rich pulse seeds and the right processing technologies make it possible to make relevant choices. The major objective of this study was to assess the impact of processing on the nutritional characteristics of beverages with a high impact on health, in particular on digestibility and specific bioactivities. The results suggest that pulse beverages are as high in protein content (3.24% w/v for chic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Chickpea milk has fewer calories than cow's milk and thus it is a more suitable drink for weight loss. Unlike dairy milk, chickpea milk does not contain lactose or gluten, therefore it reduces the risk of allergy and sensitivity in people who are lactose and gluten intolerant [21,41].…”
Section: Plant Milk Is An Alternative To Animal Milk With An Emphasis...mentioning
confidence: 99%
“…Chickpea milk has fewer calories than cow's milk and thus it is a more suitable drink for weight loss. Unlike dairy milk, chickpea milk does not contain lactose or gluten, therefore it reduces the risk of allergy and sensitivity in people who are lactose and gluten intolerant [21,41].…”
Section: Plant Milk Is An Alternative To Animal Milk With An Emphasis...mentioning
confidence: 99%
“…Protease inhibitors affect enzyme activity and amino acid intake primarily through protein-protein interactions, including trypsin inhibitors (TI) and chymotrypsin inhibitors (Bou et al, 2022). Duarte et al (2022) detected the anti-nutrient level of PBM substitutes. The results showed that the concentration of PA in the lupin beverage was higher than that in the chickpea beverage (0.83 against 0.78 g/100 mL).…”
Section: Anti-nutritional Factorsmentioning
confidence: 99%
“…Duarte et al. (2022) detected the anti‐nutrient level of PBM substitutes. The results showed that the concentration of PA in the lupin beverage was higher than that in the chickpea beverage (0.83 against 0.78 g/100 mL).…”
Section: Potential Risk Factors In Novel Synthetic Foodsmentioning
confidence: 99%